Trends and outcomes of infective endocarditis in patients on dialysis - Bhatia, Nirmanmoh (Clin Cardiol, 2017)
Dialysis patients are at high risk for infective endocarditis (IE); however, no large contemporary data exist on this issue. We examined outcomes of 44 816 patients with IE on dialysis and 202 547 patients with IE not on dialysis from the Nationwide Inpatient Sample database from 2006 thorough 2011. Dialysis patients were younger (59 ± 15 years vs 62 ± 18 years) and more likely to be female (47% vs 40%) and African‐American (47% vs 40%; all P < 0.001). Hospitalizations for IE in the dialysis group increased from 175 to 222 per 10 000 patients (P (trend) = 0.04). Staphylococcus aureus was the most common microorganism isolated in both dialysis (61%) and nondialysis (45%) groups. IE due to S aureus (adjusted odds ratio [aOR]: 1.79, 95% confidence interval [CI]: 1.73‐1.84), non‐aureus staphylococcus (aOR: 1.72, 95% CI: 1.64‐1.80), and fungi (aOR: 1.4, 95% CI: 1.12‐1.78) were more likely in the dialysis group, whereas infection due to gram‐negative bacteria (aOR: 0.85, 95% CI: 0.81‐0.89), streptococci (aOR: 0.38, 95% CI: 0.36‐0.39), and enterococci (aOR: 0.78, 95% CI: 0.74‐0.82) were less likely (all P < 0.001). Dialysis patients had higher in‐hospital mortality (aOR: 2.13, 95% CI: 2.04‐2.21), lower likelihood of valve‐replacement surgery (aOR: 0.82, 95% CI: 0.76‐0.86), and higher incidence of stroke (aOR: 1.08, 95% CI: 1.03‐1.12; all P < 0.001). We demonstrate rising incidence of IE‐related hospitalizations in dialysis patients, highlight significant differences in baseline comorbidities and microbiology of IE compared with the general population, and validate the association of long‐term dialysis with worse in‐hospital outcomes.